BTT305 – Protein Biochemistry (Biokimia Protein) - PPSKJ, Pusat Pengajian Sains Kajihayat (Universiti Sains Malaysia, 2023)
Second Semester Examination 2022/2023 Academic Session July/August 2023 BTT305 – Protein Biochemistry (Biokimia Protein) Duration : 2 hours (Masa : 2 jam)